¿Por qué se equivocó Etxepare? (notas para una historia de las tecnologías de la escritura) - Ayestarán Úriz, Ignacio (Huarte de San Juan. Filología y Didáctica de la Lengua, 1999)
In 1545 Bernard Etxepare wrote: "The Basques are appreciated the world over, but all the rest have mocked their tongue, for it was not found written on any page. Now shall they learn what a fine thing it is". But Etxepare’s prophecy was wrong. When the art of printing arrived, the Basque language didn’t "go forth into the world". This was due to technoscientific reasons. This paper analyses the history of these reasons, especially the relation between the orality of the Basque culture and the new technologies of writing.